Uma proposta de trabalho interdisciplinar empregando os temas geradores alimentos e obesidade - Soares, Max Castelhano (2010)
Currently, in the educational context, has been emphasized the importance of the teacher. It is he who should lead, with skill and competence, the process of bring the reality of the classroom for the student's reality. One way to work with science teaching in a more close to the reality of students can be through the use of instruments of their daily lives, like the comics. In contemporary world, where physical inactivity and poor nutrition are presents in the lives of adolescents, it is also important discuss in the physical education classes, the questions about health and physical well-being and mental. However, these issues are not unique demands of the physical education‟s teacher and should be worked out jointly between the different disciplines. This research was carried out from March to September 2009, with six classes of elementary school a municipal school Uruguaiana / RS. From lectures and class discussions, the students were challenged to create comics stories with the theme "Food". As a result of the work, they created of 19 comics, 04 word‟s searches, 01 activity to identify figures, and 01 short composition. These creations were analyzed and discussed in this study, and were digitized, resulting in a book, which was presented at the Interdisciplinary Educational Shows, developed by teachers and students of the school. In the collective construction‟s analysis, we find that learning became more effective, because, in fact, the knowledge developed in the course of classes are present in the comics stories and in the other activities, as confirmed by the students in some talks. Likewise, the show was instrumental in teaching perspective bring educators from different areas, through the inclusion of subjects generators, the interdisciplinary approach. In conclusion, at this perspective became possible make learning more meaningful and more enjoyable for teachers and students involved in the teaching learning.